Antibody-mediated rejection of renal allografts: diagnostic pitfalls and challenges - Novotný, M; Kment, M; Viklický, O (Physiological research, 2021)
Antibody-mediated rejection (ABMR) is a major obstacle to the long-term success in kidney transplantation. Diagnosis of ABMR is determined according to the internationally recognized Banff criteria. However, a significant proportion of patients does not meet all the defined criteria, and the outcome of such cases remains poorly understood. The histology of ABMR frequently lacks sensitivity and specificity. More importantly, mixed forms of ABMR and T cell-mediated rejection as well as findings of nonspecific injury are common in clinical settings. Donor-specific anti-HLA antibodies (DSA) are detectable only in half of the ABMR cases by histology. Prognostic role of non-HLA antibodies against various endothelial proteins has been discussed. Antibody independent NK cell activation reflecting killer-cells' inhibitory receptor incompatibility is suggested in microvascular inflammation in DSA negative patients. Molecular assessment of ABMR has been prioritized to overcome high interobserver variability and improve diagnostics in mixed forms of rejections and in DSA negative cases. Finally, donor-derived cell-free DNA detected in a recipient's peripheral blood sample has been proposed as a noninvasive marker for diagnosis of graft rejection, and thus might serve as a liquid biopsy in the near future. Despite all achievements, diagnosing ABMR in kidney allografts remains to be a challenge in a significant number of cases.
Keywords: rejekce štěpu; Kidney Transplantation; Allografts; Kidney; alografty; Isoantibodies; lidé; Graft Rejection; transplantace ledvin; ledviny; isoprotilátky; Humans